Peracetic acid as a potential treatment for amoebic gill disease (AGD) in Atlantic salmon - Stage 1 - Lazado, Carlo C.; Timmerhaus, Gerrit; Pedersen, Lars-Flemming; Pittman, Karin; Soleng, Malene; Haddeland, Sindre; Johansen, Lill-Heidi; Breiland, Mette Serine Wesmajervi; Rørmark, Lisbeth; Mohammad, Saima; Hytterød, Sigurd (Nofima, 2019)
PERAGILL is an initiative that ultimately aims to develop an alternative treatment for the currently available therapies for amoebic gill disease (AGD) that have several practical and environmental issues. Peracetic acid (PAA) is a potent oxidant with a broad spectrum of antimicrobial activity and decays into relatively safe residuals, thus, has been widely recognised as a sustainable disinfectant in aquaculture. Earlier reports on PAA underscore its potential to address the challenges of the current AGD treatments. Hence, this project aimed to establish its credentials as a chemotherapeutant for AGD. Stage 1 documented the impacts of PAA exposure on the health and welfare of salmon, its degradation kinetics and its antiparasitic activity against the Paramoeba perurans , the causative agent of AGD. There were 3 in vivo exposure experiments performed where salmon were exposed to varying levels of PAA. Experiment 1 was designed to evaluate whether previous exposure history might desensitise the responses upon re-exposure. Salmon were exposed to different nominal concentrations (0, 0.6, and 2.4 ppm) of PAA for 5 min, followed by a re-exposure to the same concentrations for 30 min 2 weeks later. Experiment 2 explored how a stressful episode before exposure might interfere with the adaptive responses to PAA. Fish were subjected to crowding stress prior to PAA exposure at 4.8 ppm for 30 min. And lastly, Experiment 3 investigated the impacts of repeated exposures to PAA. Salmon were exposed to 10 ppm PAA either for 15 min to 30 min every 3 weeks, with 3 exposures in total. Growth performance was not affected in all exposure trials. Behavioural changes such as agitation, erratic swimming, increased ventilation and loss of balance during exposure were only observed in experiment 3. No significant mortality was recorded in all experiments, and exposed fish recovered quickly after exposure as evidenced by unaffected feeding patterns. Though there were external welfare changes (e.g. skin damage, fin damage) following ...